Smartpls Moderasi Model : Determinant Kinerja Auditor - Tanjung, Juita; Sulhendri, Sulhendri; Purwanto, Edi; Rinaldo, Rinaldo (GEMA EKONOMI, 2023)
This study aims to examine the effect of leadership style, professional ethics, and organizational commitment on auditor performance with professional ethics as a moderating variable. This research belongs to the type of quantitative research. The data collection method used was a field survey method with primary data. The technique used is by distributing questionnaires to 79 respondents of external auditors who work in Public Accounting Firms in the South Jakarta area. The sampling technique used is non-probability sampling. Testing the research data is processed using SmartPLS version 33. The results of this study indicate that leadership style has a positive and significant effect on auditor performance, professional ethics has a positive and insignificant effect on auditor performance, organizational commitment has a positive and significant effect on auditor performance, leadership style has no significant effect on auditor performance. significant effect on professional ethics, organizational commitment has a positive and significant effect on professional ethics, leadership style has an effect on professional ethics is not successfully moderated by auditor performance and organizational commitment to professional ethics is moderated by auditor performance